INFORMAL COMPARISON STUDY OF FACTORS INFLUENCING ACADEMIC PERFORMANCE OF KCSE: A CASE OF IMENTI SOUTH AND IMENTI CENTRAL IN MERU COUNTY - Kimathi, Faith Kagwiria; Kibaara, Dr. Tarsilla M.; Muriungi, Dr. Pamela (IJRDO- Journal of Educational Research, 2017)
Education is the best legacy a nation can give to her citizens, especially the youth. This is because the development of any society depends much on the educational standards of the nation. The purpose of the study was to determine factors that lead to dismal performance in KCSE examinations in Imenti Central, as compared to Imenti South Sub County in Meru County. The study established that schools in Imenti South perform better than schools in Imenti Central partly because schools in Imenti South have more teachers, staffrooms, libraries, labs, books for staff and students. It was also established that schools in Imenti South Sub County perform because of high rates of student absenteeism in Imenti Central due truancy and suspension. Poor parental participation in academic work of their children and lack of communication between parents and students in Imenti Central could explain the differences between students’ the two sub-counties.